Heterogeneity of estrogen receptor α and progesterone receptor distribution in lesions of deep infiltrating endometriosis of untreated women or during exposure to various hormonal treatments. (3rd August 2018) - Brichant, Géraldine; Nervo, Patricia; Albert, Adelin; Munaut, Carine; Foidart, Jean-Michel; Nisolle, Michelle
Abstract: Deep infiltrating endometriosis (DIE) responds variably to hormonal therapy. Mutations in cancer driver genes have been identified in a fraction of the ectopic endometrial epithelial cells, suggesting a functional heterogeneity of these lesions. To evaluate the phenotype heterogeneity of cells in DIE, we measured the expression of estrogen receptor α (ERα) and of progesterone receptor (PR) in DIE of untreated women or under various treatments. We analyzed the luminal epithelial height (LEH), immunoreactive epithelial staining (IRS) and stromal staining intensity (SSI) of ERα and PR. We observed a high variability in the same gland, among distinct glands in the same sample and among distinct patients receiving the same treatment. LEH variability was primarily due to epithelial cells heterogeneity in a gland, secondarily to the glands randomly evaluated on the same section, and tertiary to the patient category. Variability in IRS and SSI scores was primarily the consequence of their heterogeneity in the same woman and to a lesser extent to variability among patients. LEH and SSI were not modified according to treatment. IRS for PR was lower in treated patients. This heterogeneity of ERα and PR distribution could explain why endocrine treatments are unable to cure this condition.